The paper chase - Thompson, Robert C.; Paul, Rodrick; Bridges, James; Twentieth Century-Fox Film Corporation; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, California : 20th Century Fox Home Entertainment, 1973)
Serius and hard-working, Hart (Bottoms) finds he must survive much more than the pressures, all-night cramming and insecurities he expected. He becomes the fearful adversary of Knightsfield, the school's most imperious, wutheringly sarcastic yet brilliant professor (John Houseman). Terrorizing some, inspiring others, the professor easily seperates the men from the boys by the time the term is over. Hart's personal relationship with knightsfield grows more complex when he discovers the girl he's fallen in love with is the professor's daughter (Lindsay Wagner).
Based on the novel by John Jay Osborn, Jr
Music, John Williams
Cast : Timothy Bottoms, Lindsay Wagner, John Houseman, Edward Herrmann, James Naughton
Keywords: Harvard Law School -- Students -- Drama; Harvard Law School -- Drama; Law teachers -- Drama; Law students -- Massachusetts -- Drama; Law -- Study and teaching -- Massachusetts -- Drama